2018
DOI: 10.1001/jamaneurol.2018.1430
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Utility of Ictal Magnetoencephalography in the Localization of the Epileptic Seizure Onset Zone

Abstract: IMPORTANCE Literature on ictal magnetoencephalography (MEG) in clinical practice and the relationship to other modalities is limited because of the brevity of routine studies. OBJECTIVE To investigate the utility and reliability of ictal MEG in the localization of the epileptogenic zone. DESIGN, SETTING, AND PARTICIPANTS A retrospective medical record review and prospective analysis of a novel ictal rhythm analysis method was conducted at a tertiary epilepsy center with a wide base of referrals for epilepsy su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 49 publications
0
40
1
Order By: Relevance
“…However, MEG signals are usually unaffected by the skull and skin, which leads to a higher spatial resolution than that of EEG ( Babiloni et al, 2009 ). Several studies have reported that MEG can localize epileptiform activity more accurately than EEG and provide reliable localization in the brain cortex ( Alkawadri et al, 2018 ; Tamilia et al, 2019 ; van Klink et al, 2019 ). Moreover, MEG has been increasingly used in the evaluation of epileptogenic foci before epileptic surgery because of its non-invasive precise localization ( De Tiege et al, 2017 ; Tamilia et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, MEG signals are usually unaffected by the skull and skin, which leads to a higher spatial resolution than that of EEG ( Babiloni et al, 2009 ). Several studies have reported that MEG can localize epileptiform activity more accurately than EEG and provide reliable localization in the brain cortex ( Alkawadri et al, 2018 ; Tamilia et al, 2019 ; van Klink et al, 2019 ). Moreover, MEG has been increasingly used in the evaluation of epileptogenic foci before epileptic surgery because of its non-invasive precise localization ( De Tiege et al, 2017 ; Tamilia et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…4). Unlike previous studies 6,7,[17][18][19][20][21][22] on focus diagnosis using DS analysis, all 19 cases analyzed were consecutive surgical cases, and their number was sufficient for statistical analysis ( Supplementary Table S2). We improved the DS analysis by introducing statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this principle, by constraining the dipole orientation parallel to cortical surface and modelling current distribution limited to the cortical surface, it is possible to precisely and efficiently calculate current distribution. In previous MEG studies 6,7,[17][18][19][20][21][22] that used DS analysis for focus diagnosis, a cortical surface model was used as the source space in the forward model ( Supplementary Table S2). However, when examining actual surgical cases, either (i) the brain structure was deformed by lesions caused, for example, by a tumor or trauma; (ii) the tumor had an epileptogenicity (e.g., dysembryoplastic neuroepithelial tumors and gangliogliomas); (iii) the epileptic focus was in a deep area, such as the medial, basal, and subcortical regions; or (iv) the focus had a complex histological structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Alkawadri et al [19] comparing interictal vs ictal MEG vs EEG reported that in 44 ictal MEGs, equivalent current dipole (ECD) analysis was possible in 29 patients (66%), of whom 8 had no clear interictal discharges in either MEG or EEG. Lobar concordance between ictal and interictal dipoles was seen in all the remaining 21 cases, in whom interictal activity was detected.…”
Section: Ictal Megmentioning
confidence: 99%